Place attachment of tourists and place meaning by residents cases from Huizhou, Anhui China - Tumanan, Mary Anne Ramos (China: University of Waikato, 2018)
This thesis analyses data derived from studies undertake at the Anhui villages of Hongcun, Xidi, and Nanping from September 2015 to April 2016, during which time the author lived in the area. The research methods adopted are thus in part ethnographic, the researcher being a 'temporary resident', and are premised on participant observation and reflexivity. They are also based on the 'pragmatic paradigm' espoused by John Cresswell and his various colleagues in that both qualitative and quantitative techniques were involved. The qualitative methods involved observation, the taking of photographs, diary keeping, informal conversations and interviews, and more formal semi-structured interviews. These interviews involved 45 residents as described in Chapter four, and supplemented with interviews with managers and government officials. The quantitative component of the research involved the use of questionnaires, for which items were derived in part from past studies in tourism, including studies previously undertake in the villages, and from observations made by the researcher and statements obtained from informants on site. the number of questionnaires analyzed included 584 completed by domestic Chinese tourists, 175 by visitors from overseas and 503 village residents. Taking the totality of the data the researcher sought to develop a gestalt perspective as she analyzed the data. The initial motivations behind the research were to analyze how place meanings, attachment , and identification evolved on the part of both residents and visitors in the context of these villages. The villages lie at a nexus of many factors. Two of the villages, Xidi and Hongcun, are UNESCO World Heritage villages, but previously had been under different forms of management. The former had been under the control of a village committee while the later had been managed by an external company. It has been suggested that Nanping could also become a UNESCO gazetted heritage site, and all three under current policy would be managed by state-owned enterprises involved in public-private partnerships. Equally , the villages represent the policies of the Chinese Communist Party in tackling the issues of rural poverty. As a consequences of these policies the villages, to various degrees, have seen population change. A third dynamic in how heritage and place meaning has evolved. The UNESCO accreditation related to Huizhou styles of architecture, but the villages are also places of social interactions of the formation of local culture and daily living, and places of negotiation between the interests of stakeholders all operating under the gaze of Beijing. Consequently, a the researcher sought to analyze the data, the focus began to shift under the Gestalten perspective she brought to bear on the issues. A key aspect in the past writings of place attachment, meaning and identification has been the ability if residents to be an effective force in the management of place, and ever since Peter Murphy's (1985) seminal book entitled Tourism: A Community Approach, it has become cliche to argue that residents must involved in the management of place if tourism is to be sustainable. But in these villages the numbers of visitors exceed a million, the tourist: resident ration is huge, and while residents are often entrepreneurial and economically benefit from tourism, a sense emerges of them feeling disempowered in the face of governmental policies. The final sections of the thesis hence become an analysis of the national and local roles of the Chinese Communist Party in the implementation of tourism policies. Again, there are gains and losses, and in terms of traditional Chines culture each represent two sides of the whole - a yin and yang- and this dialectic also informs the argument. the final sections of the thesis thus develop a concept of the yin-yang dualism of place meaning and tourism impact. It notes the internal social interactions within the village in juxtaposition with external forces of the State and globalization. It attempts to reconcile classical concepts with the pragmatism of daily implementation of tourism policies to better understand the nature of authenticity and legitimacy of the evolving tourism destination in the face of increasing numbers of visitors and the need for economic development.It propose a model that seeks to contribute to the literature by offering a new discourse on the way in which tourism policies create new dynamics in the evolution of destination management.
submitted August 2018
Thesis (Ph.D. Tourism and Hospitality Management)--University of Waikato,China.
Keywords: Place attachment -- Psychological aspects; China -- Description and travel -- Case studies; Tourism -- China -- Case studies; Heritage tourism -- China -- Case studies